2007
DOI: 10.4081/ijas.2007.s2.1167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison carcass traits of Azeri buffalo, native and crossbred (native * Holstein) male calves in west Azerbaijan-Iran

Abstract: Iran has 500thousand heads buffalo that 80percent of them distributed in North and North West of Iran and they reared as multi purpose animals providing milk and meat. Farmer believe that buffalo milk had the best quality but because of huge and large head and skin buffaloes carcass isn’t suitable that governmental programmer pay a low facilities to buffalo fattener in comparison the cattle fattener thus the objective of this investigation was to the Comparison carcass traits of buffalo, native and Nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…Dressing percentage, meat percentage and carcass meat yield are important indicators for judging the slaughter performance. Dressing percentage decreases with age, ranging from 48.73% to 54.93%, with that of adult bulls six percentage points lower than that of suckling calves, which is consistent with reports by Manafiazar et al, 2007, Rosalina et al, 2007, Rosalina et al, 2008 and Kandeepan et al (2009). Dressing percentage is closely related to variety, age, feeding levels and feeding management.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Dressing percentage, meat percentage and carcass meat yield are important indicators for judging the slaughter performance. Dressing percentage decreases with age, ranging from 48.73% to 54.93%, with that of adult bulls six percentage points lower than that of suckling calves, which is consistent with reports by Manafiazar et al, 2007, Rosalina et al, 2007, Rosalina et al, 2008 and Kandeepan et al (2009). Dressing percentage is closely related to variety, age, feeding levels and feeding management.…”
Section: Resultssupporting
confidence: 90%
“…In the pH values between biceps femoris and longissimus dorsi (P > 0.05), with pH value in the range of 6.31–6.44, which is in the range in studies by Manafiazar et al, 2007, Rosalina et al, 2007, Rosalina et al, 2008), Kumagai et al (2012), and Awan et al (2014). This may be due to a similar metabolic rate after slaughter between animal breeds.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Earlier, Lambertz et al [ 10 ] reported a higher carcass fat percentage in buffaloes following supplementation with a 2.0% body weight of concentrate, while Pimpa et al [ 37 ] failed to improve the warm and cold carcass yield of the cattle when fed with 5% fat. Nevertheless, the average carcass yield of the Murrah cross and the swamp buffaloes in this study was markedly lower than the pure-breed Murrah buffaloes, as reported by Biswas and Rajkumar [ 3 ] and Arshadullah et al [ 46 ], likely due to breed differences and the higher proportion of non-edible parts [ 16 , 47 ]. In fact, the Murrah cross in this study recorded a high carcass bone percentage ( p < 0.05).…”
Section: Discussioncontrasting
confidence: 43%